Evaluation of Surface Waters Quality Obtained from Different Sources of Mymensingh District of Bangladesh - Ferdous, Zannatul; Haque, M F; Hosain, M A; Rahman, M M; Sayed, Abu (The Agriculturists, 2016)
The present study was conducted to assess some chemical properties and heavy metals of surface waters collected from different sources at Bangladesh Agricultural University Campus and Mymensingh Sadar Upazila for common use. Twelve water samples were collected from 4 different locations during February to April 2011 for analyzing their chemical quality parameters. The recorded values of pH, EC (Electrical Conductivity), TDS (Total Dissolved Solid), DO (Dissolved Oxygen), As, Pb and Fe were found to range from 6.153 to 7.043, 0.194 to 0.679 mS/cm,106.333 to 389.333 ppm, 4.433 to 4.9 ppm, 0.064 to 1.756 ppb, 0.00053 to 0.00083 ppm and 0.567 to 1.795 ppm, respectively. pH and TDS of the surface water were within the standard value but other parameters such as As, Pb, and Fe were significantly higher than the standard for drinking water. The correlation analysis among chemical and heavy metal properties indicated that all the parameters had significant contribution to pollute the water except DO. The correlation between TDS and EC was strongly significant (r = 0.99**). pH showed positive significant correlation with EC and TDS. Fe showed negative (r = -0.636) significant correlation with As. The above findings show that the surface water in Mymensingh area is being gradually polluted by unplanned discharge of chemicals and heavy metals contained effluents. It might be concluded that the water is not so harmful yet for irrigation, aquaculture and livestock usage. The Agriculturists 2015; 13(1) 189-195